2011
DOI: 10.1080/09640568.2010.527472
|View full text |Cite
|
Sign up to set email alerts
|

Selected socio-economic factors affecting the willingness to minimise solid waste in Dhaka city, Bangladesh

Abstract: This paper examines the factors that influence the waste generation and willingness to minimise solid waste in Dhaka city, Bangladesh. Information on waste generation, willingness to minimise, socio-economic characteristics, and behaviour of the households towards solid waste management were obtained from interviews with 402 households in Dhaka city. Of these, 103 households regularly practised recycling activities. Ordinary least square (OLS) regression and logistic regression analysis were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…W i = the weight given to each factor by respondents, ranging from 1 to 5; X i = Frequency of answers to each factors Afroz et al, 2011). However, as Table 3 shows for almost all of the attributes users' value was higher than non-users.…”
Section: Respondents Perception and Opinion On Different Values Of Shmentioning
confidence: 97%
See 1 more Smart Citation
“…W i = the weight given to each factor by respondents, ranging from 1 to 5; X i = Frequency of answers to each factors Afroz et al, 2011). However, as Table 3 shows for almost all of the attributes users' value was higher than non-users.…”
Section: Respondents Perception and Opinion On Different Values Of Shmentioning
confidence: 97%
“…The index was calculated as follows (Kometa et al, 1994, Nim andAlum 1995;Afroz et al 2011;Adam et al 2013):…”
Section: Respondents Perception and Opinion On Different Values Of Shmentioning
confidence: 99%
“…These results are in line with Malik et al [8] who reported that most people in Putrajaya Malaysia were opposed to separation of household waste because it was perceived as inconvenient. Similarly, a study carried out in Dhaka City Bangladesh [58] reported that majority of people (74%) did not separate the waste they generate because of lack of time, no economic incentives and no recycling facilities. As a result, this has not contributed to environmental improvement.…”
Section: Community Participation Behaviour and Attitudes Towards Cbswmmentioning
confidence: 99%
“…This has been reflected in the available scientific literature related with MSW management in Bangladesh. A number of studies have been conducted covering a number of aspects related with MSW management issues in Bangladesh, such as characterization and factor of the MSW generation [10,[26][27][28][29], disposal status and management problems [8,[30][31][32][33][34][35], peoples willingness to pay for different wastes management option [36,37], composting aspects [26,38,39], and recycling aspects [33,40]. A few studies have been conducted to estimate electricity generation potential [41][42][43], but none of the studies is conducted to comprehensively assess the feasibility of WtE strategies in terms of energy conversion and carbon reduction from MSW management in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%